PROFITABILITY DRIVERS OF ISLAMIC COMMERCIAL BANKS IN INDONESIA : A FINANCIAL INDICATOR APPROACH - Zulfa Suhailah; Naelati Tubastuvi; Herni Justiana Astuti; Maulida Nurul Innayah (Nurul Jadid University, 2026)
This study examines the influence of internal factors such as Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operating Expenses to Operating Income (BOPO), Non-Performing Financing (NPF), and Bank Size on Profitability, represented by Return on Assets (ROA), in Islamic Commercial Banks authorized by the Financial Services Authority (Otoritas Jasa Keuangan or OJK) in Indonesia Using quarterly data spanning 2021–2024 from 14 Islamic commercial banks—yielding 206 observations through purposive sampling—and employing a Fixed Effect Model panel data regression approach, this research aims to capture financial performance dynamics in a more granular and timely manner compared to the annual data predominantly used in prior studies. The novelty of this study lies in the adoption of quarterly data, which provides greater sensitivity to short-term economic fluctuations and seasonal effects in the post-pandemic and post-merger era, as well as the explicit inclusion of Bank Size as an independent variable—rather than merely as a control variable as in most previous research—allowing for a direct examination of its role in driving profitability. The analysis results indicate that only BOPO has a significant negative effect on ROA, while CAR, FDR, NPF, and Bank Size are insignificant. Practical implications include recommendations for bank management to optimize operational cost control and for OJK regulators to strengthen adaptive policies addressing short-term economic fluctuations.